Poziom obciazen fiskalnych w Polsce po globalnym kryzysie finansowym na tle pozostalych krajow Unii Europejskiej - Adam P. Balcerzak (Institute of Economic Research (IER), 2013)
– The global financial crisis of the years 2008-2010 led to a situation, where long-term mistakes and negligence in the area of fiscal policy, on the one hand may threaten the financial stability of chosen economies of the European Union, as it is exemplified by the threat of bankruptcy of Greece, but may be also a direct threat to the stability of the euro area, and thus it can destabilize the entire European Union. In this context, the objective of this paper is to assess the fiscal burden in Poland compared to other members of the EU. Due to the fact that the level and severity of the fiscal burden in the country can be treated as a multidimensional phenomenon in the analysis as a research tool taxonomy instruments - in that case zero unitarization method - has been used. These tools has enabled the creation of a synthetic measure of development of the researched phenomenon and allowed to prepare the ranking of EU countries presenting the scope of their fiscal burden in the years 2007-2011. This allowed to capture one year before internationalization of the U.S. subprime crisis, and covered the period of the global financial crisis.
Keywords: 330; fiscal policy; fiscal burden; macroeconomics; financial crisis